Preschool Confusion Assessment Method for the Intensive Care Unit–Spanish (psCAM-ICU-S): Cross-Cultural Adaptation and Validation in Colombia - Pinzón-Casas, Edwar; Soto-Trujillo, Maira; Camargo-Agón, Laura; Henao-Castaño, Ángela; Gualdrón, Nathalie; Bonilla-González, Carolina (Frontiers in Pediatrics, 2021)
Objective: The goal of the present study was to perform a cross-cultural adaptation and clinical validation of the Preschool Confusion Assessment Method for the Intensive Care Unit–Spanish (psCAM-ICU-S) for its clinical use in the Colombian Population. Methods: We designed a Cross-cultural adaptation study followed by a cross-sectional validation study at a Single-center Pediatric Intensive Care Unit (PICU) at a University Hospital in Bogotá, Colombia. The study population was children aged from 6 months to 5 years and 11 months who had been treated in the PICU with a Richmond sedation-agitation scale score of−3 or higher. A three-phase study was carried out. The first phase comprised the application of psychometric tests on the tool. In the second phase, the psCAM-ICU-S was applied to the target population. Patients were evaluated by a nurse and a pediatric intensivist using the psCAM-ICU-S; additionally, a child psychiatrist evaluated each patient using the DSM-V criteria; the psychiatrist evaluation was chosen as the gold standard for the diagnosis of delirium. In the third phase, an evaluation of the tool's effectiveness was carried out by using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and likelihood ratios. Interrater agreement was also assessed by using the Fleiss' kappa. Results: Psychometric tests established the instrument's reliability and consistency as well as the clarity of its items. A total of 31 patients were evaluated. On average, the instrument presented a sensitivity of 93.3%, specificity of 94.8%, PPV 78%, NPV 99%, a positive likelihood ratio of 19.93, and a negative ratio of 0.07. The prevalence of delirium was 16.1% by the child psychiatrist and 25.8% using de psCAM-ICU-S. We confirmed high Interrater agreement, Kappa index (0.672–0.902). Conclusions: The psCAM-ICU-S was a valid and reliable instrument for the diagnosis of delirium in critically ill pediatric patients.